Constitutional Justice - Quiroga León, Anibal (1987)
The text describes the concept of constitutional justice, also known as constitutional jurisdiction, defining it as the set of mechanisms aimed at guaranteeing the supremacy of the Constitution within the framework of a rule of law. Its origin in modern constitutionalism is detailed, highlighting the two main systems: the American or “diffuse” system, in which any judge has the power to declare a norm unconstitutional in specific cases, and the European or “concentrated” system, which delegates this function to specialized constitutional courts. In turn, mention is made of a socialist model in which the Parliament supervises constitutionality. In the case of Peru, the author examines the historical evolution of constitutional justice and the convergence of these systems in their current model, including the creation of the Tribunal of Constitutional Guarantees. However, he also criticizes the deficiencies in its implementation, attributed to subjective factors such as insufficient training of magistrates and judges, stressing the importance of strengthening these institutions to consolidate the democratic system and guarantee the effective protection of fundamental rights.